PERAN KEPUASAN PELANGGAN DALAM MEMEDIASI PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN - Gina Jaya Artha, I Nengah Asta; Seminari, Ni Ketut (E-Jurnal Manajemen; Vol 8 No 1 (2019)DO - 10.24843/EJMUNUD.2019.v08.i01.p18, 2019)
The success of a service company is determined by the company's ability to build customer loyalty. The research was conducted at Honda Auto Global Motor Workshop using a sample size of 130 people with a non-probability form of method in the purposive sampling. Data analysis techniques used in this study are path analyis and sobel test. The results showed that service quality has a positive and significant effect on customer satisfaction, as well as on customer loyalty. NextCustomer satisfaction has a positive and significant effect on customer loyalty. Besides that, customer satisfaction is simultaneouslymediate the influence of service quality on customer loyalty. These results illustrate that the marketing environment is dynamic, so as to maintain customer loyalty, the company is expected to be able to create quality services that are in line with what is expected by customers so that satisfaction arises. Keywords : service quality, customer satisfaction, customer loyalty .